Miniatur Tuhan Dan Termenologi Teks Bible Ditinjau Dari Sudut Pandang Islam - Eko Nopriyansa (Al Hikmah, 2021)
ABSTRACT Characteristics of Religion, can not be separated from the influence of the sacred text of the scriptures as an Absolute belief and principle. The role of various initiators of religious figures in past civilizations seems to have a major influence on the future of religion. Furthermore, if we examine various religious literature, religion seems to be a spirit for world civilization, the majority of people consider that religion can be a solution and alternative in political polemics, social dilemmas to conflicts between nations. Furthermore, no less interesting is that the two religions have relevance and terminology that contain a lot of similarities, but differ in substance and point of view. the truth of knowledge, to several Prophetic legends. Departing from some previous patterns and explanations, it is the responsibility of every religious community to clarify the existence of their respective religions in accordance with their respective characteristics and beliefs, therefore, efforts in the preparation of this article are in order to explain the position of Islam as the last religion has claims to perfect and correct various deviations of the previous scriptures, especially in seeing the Manifesto of God contained in the Bible believed by Christians today as the Gospel, as well as the validity of Islamic statements in the review of the Bible. Keyword: God Miniature, Bible Text, Islam, Abstrak : Karakteristik Agama, tidak lepas dari pengaruh teks sakral kitab suci sebagai suatu keyakinan Absolut dan prinsip. Peran berbagai inisiator tokoh- tokoh agama dalam peradaban masa lampau, nampaknya memiliki pengaruh besar terhadap masa depan Agama. Lebih jauh, jika menela’ah berbagai literature keagamaan, nampaknya Agama menjadi suatu ruh bagi peradaban dunia, mayoritas manusia menganggap Agama dapat menjadi suatu solusi dan alternative dalam polemic politik, dilemma sosial hingga konflik antar bangsa. Lebih jauh, yang tidak kalah menariknya bahwah kedua Agama ini memiliki relevansi dan termenologi yang mengandung banyak sekali kemiripan, namun berbeda secara subtansi dan sudut pandang, sebut saja ketika membicarakan tokoh seperti Ibrahim, Legenda pengorbanan putra Ibrahim, Termenologi konsep teologis, kesesuaian teks dan konteks kebeneran ilmu pengatahuan, hingga pada beberapa Legenda kenabian. Berangkat dari beberapa pola dan penjelasan sebelumnya, menjadi suatu tanggung jawab setiap umat beragama untuk memperjelas eksistensi agamanya masing-masing sesuai dengan karakteristik dan keyakinan masing-masing, oleh karena itu, upaya dalam penyusunan artikel ini adalah dalam rangka menjelaskan posisi Islam sebagai Agama terakhir yang memiliki klaim menyempurnakan serta memperbaiki beragai penyimpangan kitab suci sebelumnya, terutama dalam melihat Maniatur tuhan yang terdapat dalam Al-kitab yang diyakini umat Kristen saat ini sebagai kitab Injil, serta keabsahan akan pernyataan Islam dalam tinjauan Al-kitab.